141k views
1 vote
What’s the correct answer for this?

What’s the correct answer for this?-example-1
User Itspoma
by
5.0k points

2 Answers

3 votes

Answer:

26

Explanation:

Applying the tangent-secant theorem, we get:

12^2 = 8 * (x + 10)

144 = 8x + 80

= 8x = 144 - 80

8x = 64

x = 8

Putting x = 8 in ED, which is x + x + 10, we get:

= 8 + 8 + 10

= 26

Hope this helps!

User Dlinet
by
4.4k points
4 votes

Answer:

ED = 26

Explanation:

Using tangent-secant theorem

(12)²=(8)(x+10)

144=8x+80

144-80=8x

8x = 64

x=8

Now

ED = 8+8+10

ED = 26

User LethalMango
by
4.1k points